Gingival Cyst of the Adult as Early Sequela of Connective Tissue Grafting - Mariana Gil Escalante; Dimitris N. Tatakis (Case Reports in Dentistry)
The subepithelial connective tissue graft (SCTG) is a highly predictable procedure with low complication rate. The reported early complications consist of typical postsurgical sequelae, such as pain and swelling. This case report describes the development and management of a gingival cyst following SCTG to obtain root coverage. Three weeks after SCTG procedure, a slightly raised, indurated, ~5 mm diameter asymptomatic lesion was evident. Excisional biopsy was performed and the histopathological evaluation confirmed the gingival cyst diagnosis. At the 1-year follow-up, the site had complete root coverage and normal tissue appearance and the patient remained asymptomatic.